A Review of the Impact of Preparation on Stability of Carbon Nanotube Nanofluids - Muhammad Noor Afiq Witri, Muhammad Yazid; Nor Azwadi, Che Sidik; R., Mamat; G., Najafi (Elsevier, 2016)
Carbon nanotube (CNT) has the highest thermal conductivity among the nanoparticles that were discovered so far. Attempts to utilize them as heat transfer fluids by dispersing them into any kinds of base fluids called CNT nanofluids have been thoroughly conducted. However, one of the challenges faced by many researchers in applying their prepared CNT nanofluids is to maintain its homogeneous state and long-term stability. This paper presents an inclusive review on the preparation techniques and the reported period of stability of stationary CNT nanofluids. The characteristics of available treatment such as chemical treatment (covalent and non-covalent) and physical treatment methods have been systematically analyzed. Finally, the challenges and future trends of CNT nanofluids are discussed.